Mozart's The magic flute - Schikaneder, Emanuel, 1751-1812 (Opera Journeys, 2001)
Annotation -- Engaging Commentary and Analysis about the composer, the opera and its characters. -- Story Narrative with Music Highlight Examples -- A complete Libretto (newly translated) that incorporates Music Highlight Examples -- A Discography -- A Videography -- A Dictionary of Opera and Musical Terms Each Opera Classics Library edition is a comprehensive guide and complete analysis and evaluation of a specific opera; each is a unique "encyclopedia" that integrates important and pertinent information about each timeless classic. The objective of Opera Classics Library is to unlock opera's mysteries for the general audience, and enlighten and educate. Understanding and knowledge are the master keys to enhance enjoyment and appreciation of this great art form. Mozart's The Magic Flute was aptly described by the great German Romanticist Wolfgang von Goethe: "It takes more culture to perceive the virtues of The Magic Flute text than to point out its defects." Mozart's sublime score magnificently integrates the underlying intellectual themes of this opera. Its fairy tale involving the moral forces of good against evil, political and social allegory of late eighteenth century Austrian politics, archetypal story of man's struggle for consciousness and awareness, and exposition of the Enlightenment ideals of Freemasonry
Keywords: Mozart, Wolfgang Amadeus, -- 1756-1791. -- Zauberflöte.; Zauberflöte (Mozart, Wolfgang Amadeus); Operas -- Librettos.; Opéras -- Livrets.; MUSIC -- Genres & Styles -- Opera.; Operas -- Librettos